Women's Agency in Preserving Ngasa Gandoang Mountain Alms Ritual - Ninawati Syahrul; Sastri Sunarti; Priscila Fitriasih Limbong; Syahrial Syahrial (Leksema: Jurnal Bahasa dan Sastra, 2026)
Investigations into the contributions of women in safeguarding indigenous oral traditions, especially within sacred ceremonies, remain comparatively scarce. This investigation underscores women's agency as cultural stewards in the Ngasa Gandoang Mountain Alms ritual in Salem, Brebes, Central Java, which is deeply intertwined with local ecospirituality. Employing the theoretical lenses of gender agency and oral tradition, this study seeks to examine women's involvement in sustaining and reproducing ritual significance, investigate the elements that empower women to attain prominence in a cultural-religious domain typically dominated by men, and assess women's approaches in upholding the endurance of tradition amid currents of societal transformation and modernization. The methodology incorporates feminist ethnography, encompassing in-depth interviews, participant observation, and source triangulation. Findings indicate that women occupy a pivotal role in upholding spiritual principles, fostering collective remembrance, directing ritual proceedings, and deciphering symbolic interpretations. The originality of this research resides in the reinterpretation of Ngasa Gandoang Mountain Alms through a gender lens that portrays women as proactive contributors to informal cultural transmission. The study's implications encompass the necessity for women's integration into cultural conservation initiatives, the formulation of role-oriented educational and archival strategies, the incorporation of gender viewpoints in sustainable tourism, and avenues for additional inquiries to investigate analogous dynamics in diverse regions or modernization contexts.